DISTRIBUIÇÃO ESPACIAL DA CONCENTRAÇÃO DE NUTRIENTES EM SEDIMENTOS NA LAGUNA HIPERSALINA DE ARARUAMA – RJ, BRASIL - Silva, Kaylanne Montenegro; Guimarães, Teresa Cristina; Wasserman, Julio Cesar (Geochimica Brasiliensis, 2019)
The present study was carried out in Laguna de Araruama, Rio de Janeiro. Pollution in the lagoon has hampered the ecosystem structure and caused the eutrophication process to intensify. In order to improve water quality, it is proposed to open channels of the lagoon with the sea, but may result in the remobilization of the nutrients in the sediment to the water column. Considering the importance of sediment as a nutrient storage compartment, the objective of this study was to determine nutrient concentrations in sediments and interstitial water and their distribution in the sediments. Measurements of pH and Eh were made in the sediment, conductivity and temperature along the water column. The granulometry was determined and the concentrations of ammonium, nitrite, nitrate and phosphate in the interstitial water were determined, and the total concentrations of phosphorus, nitrogen and carbon in the sediments. Considering the granulometric results, most of the lagoon has sandy formations. The sediment presented temperatures between 22 °C and 25 °C, basic pH (7.1 - 8.2) and reducing characteristics (-400mV). In the stations near São Pedro da Aldeia and Araruama, there are high levels of total nitrogen in the sediment due to the high amount of sewage discharged into the rivers that flow into the lagoon. High concentrations of total phosphorus were also found in the region of the Itajuru Channel, closer to the sea, which due to its lower salinity has higher primary productivity. It is concluded that the lagoon presents a high degree of pollution by nutrients, in specific points, due to the contributions caused by the discharge of sewage